Simple fabrication method for a porous poly(vinyl alcohol) matrix by multisolvent mixtures for an air-exposed model of the lung epithelial system - Chae, Su-Kyoung (Langmuir : the ACS journal of surfaces and colloids, 2014)
We introduce a simple and easy method for fabricating a thin and porous matrix that can be used as an extracellular matrix (ECM). A porous poly(vinyl alcohol) (PVA) matrix was created through recrystallization by multiple solvents under distilled water (DW), isopropyl alcohol (IPA), and a combination of DW and IPA. The crysatllization was driven by precipitating and dissolving a solute in a solution of a solvent and a nonsolvent, which induced the formation of microspheres in the IPA. The crystal structure depended on the ratio of the solvent/nonsolvent and the concentration of the PVA aqueous solution; these properties were used to tune the thickness, size, and porosity of the matrices. The resulting PVA matrix was chemically stabilized through a reaction with glutaraldehyde in the IPA solution. We demonstrated that a very thin and porous PVA matrix provided an effective functional model of the lung epithelial system. Lung epithelial cells (A549) displayed a high affinity for this matrix, which was permeable to the culture medium. These properties facilitated culturing under the air environment